(3fbO GdWQjb GdGbJUGOj cCOGI Edi GdGJMGO GdSjGSj (B/s - (3GdHjWGQ, fOjes ((3HjQhJ(B: s (3HjSGf ddfTQ hGdJhRjY(B, s, 2002)
(3GdfbO GdSjGSj(B:(3GdJfGbV Hjf GdYbdGfjI GdGbJUGOjI hGdJYOO GdSjGSj,aTd GdeMGhdGJ GdGbJUGOjI cCOGI ddEJMGO GdSjGSj,ChdhjI GdYed GdSjGSj aj GdJfSjb GdGbJUGOj,EbdjejI Gdeaghe GdGbJUGOj Mhd GdWQjb Edi GdhMOI,ef GdJfejI GdGbJUGOjI Edi GdOhdI GdKhQjI,GdfbO GdShSjhdhLj GdJGQjNj(B:(3GdfbO GdShSjhdhLj GdJGQjNj(B:(3fbO ShSjhdhLj YGe,GdJeKjd Ydi GdfbO GdShSjhdhLjs
Keywords: (3GdGJMGO GdShajGJjs; (3GdGbJUGOs; (3GdhMOI GdSjGSjIs